Rotavirus in developing countries: molecular diversity, epidemiological insights, and strategies for effective vaccination - Sadiq, Asma; Khan, Jadoon (Frontiers in Microbiology, 2024)
Rotavirus (RV) causes the loss of numerous children's lives worldwide each year, and this burden is particularly heavy in low-and lower-middle-income countries where access to healthcare is limited. RV epidemiology exhibits a diverse range of genotypes, which can vary in prevalence and impact across different regions. The human genotypes that are most commonly recognized are and G12P[8]. The diversity of rotavirus genotypes presents a challenge in understanding its global distribution and developing effective vaccines. Oral, live-attenuated rotavirus vaccines have undergone evaluation in various contexts, encompassing both low-income and high-income populations, demonstrating their safety and effectiveness. Rotavirus vaccines have been introduced and implemented in over 120 countries, offering an opportunity to assess their effectiveness in diverse settings. However, these vaccines were less effective in areas with more rotavirus-related deaths and lower economic status compared to wealthier regions with fewer rotavirus-related deaths. Despite their lower efficacy, rotavirus vaccines significantly decrease the occurrence of diarrheal diseases and related mortality.They also prove to be cost-effective in regions with a high burden of such diseases. Regularly evaluating the impact, influence, and cost-effectiveness of rotavirus vaccines, especially the newly approved ones for worldwide use, is essential for deciding if these vaccines should be introduced in countries. This is especially important in places with limited resources to determine if a switch to a different vaccine is necessary. Future research in rotavirus epidemiology should focus on a comprehensive understanding of genotype diversity and its implications for vaccine effectiveness. It is crucial to monitor shifts in genotype prevalence and their association with disease severity, especially in high-risk populations. Policymakers should invest in robust surveillance systems to monitor rotavirus genotypes. This data can guide vaccine development and public health interventions. International collaboration and data sharing are vital to understand genotype diversity on a global scale and facilitate the development of more effective vaccines.